2017
DOI: 10.1002/jwmg.21264
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of translocated greater sage‐grouse to population vital rates

Abstract: Range‐wide declines of greater sage‐grouse (Centrocercus urophasianus; sage‐grouse) populations have been attributed to long‐term habitat alteration and fragmentation. In areas that still exhibit suitable habitats and where population declines have been attributed to other threats (e.g., invasive predators), managers have successfully used translocations to augment declining wildlife populations. However, translocations to augment sage‐grouse populations have had limited success and the relative contribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Baxter et al (2008) reported survival of 0.60 (95% CI = 0.515–0.681) for female greater sage‐grouse in Utah during the first year following translocation. Also in Utah, survival of resident greater sage‐grouse (0.46, 95% CI = 0.31–0.63) was higher than survival of translocated sage‐grouse (0.36, 95% CI = 0.25–0.49; Duvuvuei et al 2017). Ebenhoch et al (2019) reported that in Washington, translocated male GRSG experienced lower survival than females.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Baxter et al (2008) reported survival of 0.60 (95% CI = 0.515–0.681) for female greater sage‐grouse in Utah during the first year following translocation. Also in Utah, survival of resident greater sage‐grouse (0.46, 95% CI = 0.31–0.63) was higher than survival of translocated sage‐grouse (0.36, 95% CI = 0.25–0.49; Duvuvuei et al 2017). Ebenhoch et al (2019) reported that in Washington, translocated male GRSG experienced lower survival than females.…”
Section: Discussionmentioning
confidence: 98%
“…Translocations were commonly used to manage North American grouse species, including greater sage‐grouse ( Centrocercus urophasianus ), with variable success (Reese and Connelly 1997). Recent evaluations of greater sage‐grouse translocation efforts have reported on demographic metrics as measures of success (Baxter et al 2008, Bell and George 2012, Gruber‐Hadden et al 2016, Duvuvuei et al 2017, Ebenhoch et al 2019). Among vital rates, survival (particularly female survival) strongly influenced long‐term population stability and growth rates (Taylor et al 2012, Dahlgren et al 2016).…”
mentioning
confidence: 99%
“…Translocation has been used as a management tool to augment declining sage-grouse populations across their range (Reese and Connelly, 1997;Baxter et al, 2008Baxter et al, , 2013Duvuvuei et al, 2017). Sage-grouse populations have undergone severe declines since the 1960s (Garton et al, 2011;Coates et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals that stay in the release area often exhibit lower survival and reproductive rates than individuals within source populations (Patterson 1952, Toepfer and Eng 1990, Snyder et al 1999. Specifically, translocated pre-breeding females often fail to breed at the restoration site in the first year of their translocation (Baxter et al 2008(Baxter et al , 2013Duvuvuei et al 2017). Furthermore, extensive post-release movements, which are common among translocated grouse species, have been demonstrated to reduce survival (Kurzejeski andRoot 1988, Ebenhoch et al 2019).…”
mentioning
confidence: 99%